2000
DOI: 10.1103/physrevlett.85.4128
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption on Carbon Nanotubes: Quantum Spin Tubes, Magnetization Plateaus, and Conformal Symmetry

Abstract: We formulate the problem of adsorption onto the surface of a carbon nanotube as a lattice gas on a triangular lattice wrapped around a cylinder. This model is equivalent to an XXZ Heisenberg quantum spin tube. We find density plateau structures for armchair, zigzag, and chiral nanotubes. The zigzags are special and have extensive zero temperature entropy plateaus in the classical limit. Quantum effects lift the degeneracy, leaving gapless excitations described by a c = 1 conformal field theory with compactific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…Instead, it is a crystal containing a dilute array of quantum-fluctuating strings, which we call "stripe-walls" since each has a deficit of fermion density and is a domain wall of the crystal order 29 . There is no previous literature on such stripewalls in the case of the triangular lattice for fermions, only for hardcore bosons (in the context of 4 He adsorbed on carbon nanotubes 20,21 . Nevertheless, it was shown in Ref.…”
Section: Van Eertenmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, it is a crystal containing a dilute array of quantum-fluctuating strings, which we call "stripe-walls" since each has a deficit of fermion density and is a domain wall of the crystal order 29 . There is no previous literature on such stripewalls in the case of the triangular lattice for fermions, only for hardcore bosons (in the context of 4 He adsorbed on carbon nanotubes 20,21 . Nevertheless, it was shown in Ref.…”
Section: Van Eertenmentioning
confidence: 99%
“…Past studies 15,20 showed that a single stripe-wall can be mapped exactly to a one-dimensional chain with noninteracting spinless fermions at half filling, with their hopping amplitude equal to t = 1. This mapping remains valid in the supersymmetric case, since all the accessible configurations for the stripe-wall have equal (and maximal) potential energy F .…”
Section: Van Eertenmentioning
confidence: 99%
“…35 Finally, the same code is adaptable, almost without modifications, to the triangular lattice. That may model 3 He or 4 He atoms adsorbed on graphite or on carbon nanotubes, 19,20 which implement a periodic boundary condition in one direction. s h (L x , L y ) be the number of basis states (per k vector) in a configuration with s stripes and h holes on it.…”
mentioning
confidence: 99%
“…This paper contains a detailed account of the results in Ref. [10], as well as new analytical results that explain the numerical findings of the previous work.…”
Section: Introductionmentioning
confidence: 60%